Health education actions for the elderly in Primary Health Care: an integrative review (Research, Society and Development, 2021)
The aim of this study is to carry out an integrative literature review on health education for the elderly in the context of primary health care. To answer the research question - how is health education related to the health of the elderly being carried out in the context of primary health care, bibliographic data were collected in the Scientific Electronic Library Online Literature, Latin American and Caribbean databases in Health Sciences, Virtual Health Library, the PubMed search portal of the Medical Literature Analysis and Retrieval System Online database and the journal portal of the Coordination for the Improvement of Higher Education Personnel. Articles published in Portuguese, English or Spanish and available in full between 2016 and 2021 were considered. After analyzing the 14 selected studies, the publications were divided into health education aimed at the elderly and health professionals. When answering the research question, results were obtained that deviate from the ideal proposal in the context of public health, but that the objective is being pursued and implemented in primary health care. With this, it was possible to infer the great importance that the components of primary care have in relation to health education in the context of elderly health, for example, practices based on the subject's clinic, under the biopsychosocial model; multidisciplinarity and comprehensive care. In addition, the difficulties and impasses that the teams have to offer comprehensive care were described.